The Influence of Interpretation, Commitment and Nature Conservation Knowledge on Pro-Conservation Behavior Among Malaysian Students - Suhaimi Taat, Muhamad; Fazley Charlie, Elver; Hanisdah Saikim, Fiffy (International Journal of Engineering and Technology, 2018)
Human behavior has caused negative impact on our environment. The exploration, exploitation and destruction of our planet occurred merely to satisfy the desires of human being. Thus, to sustain a better future particularly in terms of healthy lifestyles and maintain environmental sustainability, the human behavior towards conservation must be changed. Therefore, this quantitative research involved secondary students in order to identify and explore the level and influence of students’ interpretation, commitment, knowledge and pro-conservation behavior. The respondent consists of 500 students from selected urban secondary schools in Sabah, Malaysia. Questionnaire adapted from previous researches was the instrument used to collect the data. Descriptive and inferential statistics were used to analyze the data. The results revealed that there was significance influence of student’s knowledge and commitment on pro-conservation behavior. The research findings revealed that the students’ interpretation, commitment, nature conservation knowledge and their behavior were important and needed more attention from various parties in order to develop their lifelong attitude towards environment and biodiversity conservation. Hence, the environmental organizations need to design and organize a lot of conservation programmes in schools in order to promote conservation and build positive impact on the students’ behavior towards environment and biodiversity conservation.